Perseroan Terbatas sebagai Institusi Kegiatan Ekonomi yang Demokratis - Johari Santoso (Fakultas Hukum Universitas Islam Indonesia, 2000)
The presence of the company limited acts is aconcret step from the government in the effort of giving a guide for business people in running their commercial activities and this case it support the Indonesia business people in order to thing progressively. It is aimed that company limited is as an institution of transparancy and efficiency can be achieved by a company limited.